The Effects of Work-Family Conflict and Facilitation on Turnover Intentions: The Moderating Role of Core Self-Evaluations - Karatepe, Osman M.; Azar, Arezou Khabbaz (Routledge Journals, Taylor & Francis Ltd, 2013)
The purpose of this study is to examine core self-evaluations as a moderator of the effects of work-family conflict, family-work conflict, work-family facilitation, and family-work facilitation on turnover intentions. This study also investigates the effects of two directions of conflict and facilitation on turnover intentions. Based on data collected from a sample of full-time frontline hotel employees in Iran, the previously mentioned relationships were tested using hierarchical multiple regression analysis. The results reveal that core self-evaluations strengthen the negative effects of work-family facilitation and family-work facilitation on turnover intentions. The results further indicate that work-family conflict and family-work conflict exacerbate turnover intentions, while only family-work facilitation alleviates turnover intentions. Implications of the findings are discussed, and their future research directions are offered.
Keywords: core self-evaluations; Iran; turnover intentions; work-family conflict; work-family facilitation